2003
DOI: 10.1161/01.cir.0000095796.45180.88
|View full text |Cite
|
Sign up to set email alerts
|

Catheter Ablation for Paroxysmal Atrial Fibrillation

Abstract: Background-Segmental ostial catheter ablation (SOCA) to isolate the pulmonary veins (PVs) and left atrial catheter ablation (LACA) to encircle the PVs both may eliminate paroxysmal atrial fibrillation (PAF). The relative efficacy of these 2 techniques has not been directly compared. Methods and Results-Of 80 consecutive patients with symptomatic PAF (age, 52Ϯ10 years), 40 patients underwent PV isolation by SOCA and 40 patients underwent LACA to encircle the PVs. During SOCA, ostial PV potentials recorded with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
186
2
4

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 798 publications
(200 citation statements)
references
References 31 publications
8
186
2
4
Order By: Relevance
“…The current study did not randomize patients without linear lesions, thereby precluding comparisons with techniques solely involving PV isolation. Given the concerns regarding potential complications, more extensive posterior LA ablations (as opposed to superior to inferior PV linear lesions alone) were not performed, although this technique may potentially increase single-procedure success rates (3)(4)(5). Also, alternate ablation strategies such as ablation of complex fractionated atrial electrograms, as described by Nademanee et al (9), in addition to PV isolation, may potentially reduce the need for repeat procedures, but this was not evaluated in our patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The current study did not randomize patients without linear lesions, thereby precluding comparisons with techniques solely involving PV isolation. Given the concerns regarding potential complications, more extensive posterior LA ablations (as opposed to superior to inferior PV linear lesions alone) were not performed, although this technique may potentially increase single-procedure success rates (3)(4)(5). Also, alternate ablation strategies such as ablation of complex fractionated atrial electrograms, as described by Nademanee et al (9), in addition to PV isolation, may potentially reduce the need for repeat procedures, but this was not evaluated in our patients.…”
Section: Discussionmentioning
confidence: 99%
“…Ablation strategies that incorporate LA linear lesions appear to have higher success rates than PVI alone (3)(4)(5)7). The technique of performing wider linear ablations in the LA may aid in targeting different substrates that help to maintain or perpetuate AF.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2,3 However, it has recently been reported that circumferential LA ablation is more effective in eliminating AF than PVI. 4,5 The incremental efficacy of circumferential LA ablation has been suggested to be attributable to a wide reduction in the anatomical and electrical substrate, that is, atrial debulking. 6,7 On the other hand, LA enlargement is accompanied by structural remodeling associated with the substrate of AF.…”
Section: Introductionmentioning
confidence: 99%